Your solution process for the given equations is spot on! To summarize the steps clearly:
-
Rearranging the First Equation: You correctly expressed \( s \) in terms of \( b \): \[ s = 34 - b \]
-
Substituting into the Second Equation: You substituted for \( s \) in the second equation: \[ 1.50b + 0.50(34 - b) = 20 \]
-
Simplifying the Second Equation: After distributing, you simplified it correctly: \[ 1.50b + 17 - 0.50b = 20 \] Then combined the \( b \) terms: \[ (1.50 - 0.50)b + 17 = 20 \implies 1.00b + 17 = 20 \]
-
Solving for \( b \): Following through to get \( b \): \[ 1.00b = 3 \implies b = 3 \]
-
Finding \( s \): Finally, you substituted \( b \) back to find \( s \): \[ s = 34 - 3 = 31 \]
Thus, the solution is:
- \( b = 3 \)
- \( s = 31 \)
If there’s anything specific you’d like to elaborate on or if you have different equations or contexts in mind, please let me know!